Stages of integration scenarios with strategic management From the perspective of study the historical development of scenarios - العنزي سعد; السعيدي يعرب عدنان (Journal of Economics and Administrative Sciences, 2014)
Purpose: The present study seeks to examine various history stages in which undergone by the concept of scenarios, and development of this concept to integration with the strategic management practices: Methodology: The current study relied on a literature review and approach in providing total picture of different stages undergone by this concept. The main results: the scenarios did not reach maturity in their quest for integration with strategic management, and still need a great effort for the maturation of this thought in the framework of strategic management, and through it can contribute in creating important knowledge evolution. Originality and value: providing a contemporary model linking the roots of this concept and current practices that take place in an advisory organization in different countries of the world, and to clarify the philosophy of this concept within different time periods.